Exploring Finnish Education Through the Lens of Naturalistic Inquiry - Younglong Kim; Katherine Curry; Jentre Olsen; Jessica Hogaboom (Journal of Research in Education and Pedagogy, 2026)
Despite growing interest in qualitative research approaches, practitioner-scholars often lack accessible, field-based guidance for conducting naturalistic inquiry in authentic educational settings. This gap highlights the need for research that is both theoretically grounded and methodologically transparent. Grounded in naturalistic inquiry, this study investigates how such inquiry can be effectively designed and implemented within an international educational context through a qualitative case study conducted in Finland. Data were collected during a two-week immersive field experience and include field notes, reflective journals, informal conversations, practitioner presentations, focus group interviews with students, and photographic artifacts. Analysis was conducted using the constant comparative method alongside ongoing reflexive practices, with attention to credibility, transferability, dependability, and confirmability. Findings address two research questions by illustrating both the implementation and outcomes of naturalistic inquiry. This study seeks to answer two main research questions: 1) How can naturalistic inquiry be practically designed and implemented by a practitioner-researcher in an international educational fieldwork context? and 2) What themes emerge from the implementation of naturalistic inquiry in an international educational fieldwork context, and how do they reflect key values and practices in Finnish education? To answer the research questions, first, the study outlines key methodological components, including site entry, prolonged engagement, emergent design, reflexivity, and triangulation of data sources. Second, three central themes emerged that reflect core features of Finnish education: (1) trust as a foundation of educational relationships and professional autonomy, (2) the integration of play and emotional development in early childhood education, and (3) structural supports that enable equity, adaptability, and teacher professionalism. This study contributes to the literature by offering a transparent, practice-oriented account of naturalistic inquiry in an international setting. It provides concrete methodological guidance for practitioner-researchers while also highlighting the cultural and systemic conditions that shape educational practice in Finland.